Psikologi Manajemen dalam Pendidikan dan Organisasi: Tinjauan Sistematis terhadap Peran Motivasi, Kepemimpinan, dan Kinerja - Fermy Anggelia Putry; Saadah Saadah; Mualimin Mualimin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Management psychology is an approach that plays a crucial role in understanding individual and group behavior within organizations, particularly in the ever-evolving educational and work environments. The application of psychological principles to management practice is believed to improve performance, leadership effectiveness, and create a more conducive work and learning environment. This study aims to examine the development of trends, approaches, and key findings in the study of management psychology through a literature review. Furthermore, this study also seeks to answer two research questions: (1) how have management psychology research trends developed over the past five years, and (2) what are the key findings in the educational and organizational contexts. The method used is a qualitative approach by searching various literature sources through the Google Scholar and Publish or Perish (PoP) databases, using the keyword